Penerapan Strategi Think, Talk, Write Dalam Kosa Kata Bahasa Inggris Dengan Menggunakan Film - Nuary, Ibrahim Guntur (Prosiding University Research Colloquium, 2018)
English language indeed is international language, but in Indonesia itself to mastering English language it’s hard to do, because of the lack of vocabulary. Vocabulary is the important part to mastering English language. To gain the vocabulary, there are many ways, one of them is watching movie. This research aimed to find out the learners in XI IPA 1 and XI IPA 2 grades how they gain the vocabulary through subtitled movie by using think, talk, write strategy. The data will be searched by qualitative descriptive. The data will be taken from the movie and teacher perspective about the strategy that teacher did. The result of this study to know how much the learners between male and female gain the vocabulary through subtitled movie by using think, talk, write strategy. The learners female and male taken two class and between learners male and female the class is not separated. The movie entitled “Frozen”. From the movie, the learners should be written the vocabulary what they got from the movie. The class is devided into five groups, then all of groups should provide the words they got from the movie and then mention the words to other groups in order to the groups know the words from other groups and its strategy was really works to make students got the words a lot from the movie. The result of this study is the learners got a lot of vocabularies between XI IPA 1 and XI IPA 2 grades through TTW strategy by using movie and the teacher gave the feedback of vocabulary from the movie. Such as the words of worth, accident, gates staff,and party from the movie.